Resilience and psychological distress in pregnant women during quarantine due to the COVID-19 outbreak in Spain: a multicentre cross-sectional online survey - Daniel María Lubián López; Carmen Aisha Butrón Hinojo; Jose Eduardo Arjona Bernal; María Fasero Laiz; José Alcolea Santiago; Virginia Guerra Vilches; Marta Casaus Fernández; Ana Bueno Moral; Antonio Olvera Perdigones; Begoña Rodríguez Rodríguez; Andrés Cuevas Palomino; Jesús Presa Lorite; et al. (Taylor & Francis Group, 2021)
Purpose To examine the prevalence of depressive and anxiety symptoms and the corresponding risk factors among pregnant women during the confinement due to the COVID-19 outbreak in Spain. Materials and methods Between 15 April and 14 May 2020, a multicentre cross-sectional survey was performed to study depression, anxiety and resilience in a sample of Spanish pregnant women during the lockdown set up by the Government in response to COVID-19 pandemic outbreak. We designed an anonymous online self-administered questionnaire (https://bit.ly/34RRpq1) that included the Spanish validated versions of the Edinburgh Postpartum Depression Scale (EPDS), the State-Trait Anxiety Inventory (STAI) and the Connor-Davidson Resilience 10-items Scale (CD-RISC-10). Results A total of 514 pregnant women completed the survey. 72.8% had been confined < 40 days and 27.2% between 41 and 60 days. 182 (35.4%) participants scored over 10, with 21.3% scoring over 13 (75th Percentile) in depressive symptoms rates. We found high trait and anxiety scores, with 223 (43.4%) and 227 (44.2%) pregnant women scoring over the trait and state mean scores. Neither depression, anxiety or resilience levels showed any significant correlation with the length of confinement. We found low CD-RISC-10 scores. Conclusions We found a high prevalence of depression and anxiety symptoms during the quarantine, although we did not find an increased prevalence of psychological distress according to length of home confinement. Resilience correlated negatively with depression and anxiety.